Co-operative difference and organizational commitment: The filter of socio-demographic variables. Issue 4 (21st February 2021) - Marcoux, Gilles; Guihur, Izold; Leclerc, André
Abstract: Even though several differences exist between co-operatives and capitalist enterprises, such as the democratic governance style of the co-operatives, both types of enterprises compete with each other. In this context, how can the co-operatives distinguish themselves from private enterprises? Based on the AMO bundles model (for Abilities, Motivation and Opportunity to participate) and on the three-component model of organizational commitment, this study collected data from 578 respondents of financial service co-operatives in eastern Canada. This research had two primary objectives. First, it seeks to examine if employees perceive a co-operative difference through HRM practices which influences their commitment. Second, it aims to evaluate the relations between HRM practices, employees' perception of a co-operative difference, and their organizational commitment through the influence of some socio-demographic variables. The main findings are that: (1) the employees perceived a co-operative difference through HRM practices that influenced their commitment; (2) the more the employees had work experience, the more they perceived a co-operative difference, and the more they displayed affective and normative commitment; (3) the higher the hierarchical status of the employees, the less they displayed calculative commitment; (4) the employees with union membership displayed lower affective and normative commitment.